2020
DOI: 10.1002/rcs.2206
|View full text |Cite
|
Sign up to set email alerts
|

An early experience with the Senhance surgical robotic system in colorectal surgery: a single‐institute study

Abstract: Background We present our initial single‐centre experience with Senhance surgical robot‐assisted colorectal surgery and examine its safety and feasibility. Methods From June 2019 to December 2019, patients who underwent Senhance surgical robot‐assisted colorectal surgery in our hospital were retrospectively analysed. We focused on the short‐term outcomes. Results In total, 46 patients were enrolled in the study. Colorectal cancer was the most common indication for surgery (39 patients). The median total operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Spinelli et al 6 and Samalavicius et al 7 have reported from Europe on surgery using this system for colorectal cancer; however, some reports indicate that lymph node dissection was performed in vitro because of a small number of cancer cases. In Asia, Lin et al 8 from Taiwan recently reported 46 cases of colorectal resection, and the short‐term results of colorectal cancer, which accounted for 39 cases, showed attention to indications and patient selection. In the short‐term results of 55 patients who underwent colorectal cancer surgery by using this device in our department, no problems were observed with regards to bleeding volume, dissection range, number of dissected lymph nodes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Spinelli et al 6 and Samalavicius et al 7 have reported from Europe on surgery using this system for colorectal cancer; however, some reports indicate that lymph node dissection was performed in vitro because of a small number of cancer cases. In Asia, Lin et al 8 from Taiwan recently reported 46 cases of colorectal resection, and the short‐term results of colorectal cancer, which accounted for 39 cases, showed attention to indications and patient selection. In the short‐term results of 55 patients who underwent colorectal cancer surgery by using this device in our department, no problems were observed with regards to bleeding volume, dissection range, number of dissected lymph nodes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…colorectal surgery. 82 The research team retrospectively analyzed 46 patients and effectively validated the feasibility of the Senhance® robotic platform in colorectal surgery.…”
Section: General Surgery Robotmentioning
confidence: 99%
“…successfully completed a double‐port sigmoid resection using the Senhance® robotic platform without any postoperative complications 81 . Lin et al similarly did a single‐center study on the safety and efficacy of the Senhance® robotic platform applied to colorectal surgery 82 . The research team retrospectively analyzed 46 patients and effectively validated the feasibility of the Senhance® robotic platform in colorectal surgery.…”
Section: Status Of Research On Classification Of Surgical Robotsmentioning
confidence: 99%
“…Several studies have reported that the new Senhance® robotic platform is safe and feasible for colorectal cancer surgery. [48][49][50]…”
Section: Robotic Systems Other Than the Da Vinci®mentioning
confidence: 99%